PEMBERDAYAAN TANAMAN Moringa Oleifera Lamk. (KELOR) PADA MASYARAKAT DUSUN TALANGSARI DESA RINGINKEMBAR KECAMATAN SUMBERMANJING WETAN KABUPATEN MALANG - Mahmudah, Rif'atul; Yulianti, Eny; Hanapi, Ahmad (JRCE (Journal of Research on Community Engagement), 2019)
Kelor is a nutrient-rich plant that can be used for food, medicine, fertilizer as well as customary rituals and is easy to cultivate, especially in tropical climates. The geographical condition is quite fertile and the economic community of Talangsari Village Ringin twin Subdistrict Sumbermanjing Wetan Malang Regency which generally middle down with the majority work as farmers make the welfare of the community Talangsari Hamlet relatively less due to low education, and health. Community empowerment is done by counseling, socialization, training to the community about the cultivation and nutrition of moringa plants to improve nutrition, as herbal medicine and organic liquid fertilizer and then conducted monitoring and evaluation. The result of the research shows that the increasing of interest for the cultivation of moringa kelor with the growing number of kelor planted, the effectiveness of kelor leaf extract as a natural fertilizer, in addition leaf kelor proven to alleviate various diseases such as uric acid and diabetes.